Public Street Lighting Planning (PJU) Using New and Renewable Energy in Tanjung Gusta Village, Hamlet III, Sunggal District - ramadhan, ilyasa; Rahmaniar, Rahmaniar; Dalimunthe, Erpandi (Universitas Nurul Jadid, 2025)
Indonesia has great potential in renewable energy, especially solar energy, due to its geographical location in the tropics. This research aims to plan an efficient and sustainable Public Street Lighting (PJU) system in Tanjung Gusta Village, Sunggal District, by utilizing new and renewable energy (NRE). Tanjung Gusta Village has a need for adequate street lighting to improve the safety, mobility, and quality of life of the community. The research method includes field surveys to analyze conditions, calculation of lighting needs based on applicable standards, and PJU system design using NRE. The results of the study show that the PJU system with solar power is the most suitable solution for Tanjung Gusta Village, taking into account the availability of resources. The planning of this solar PJU system includes the selection of the type of lamp to be used, determining the capacity of the solar panel and battery, and calculating the optimal layout and height of the light pole.